Generalised magnetisation-to-singlet-order transfer in nuclear magnetic resonance. Issue 17 (24th April 2020) - Bengs, Christian; Sabba, Mohamed; Jerschow, Alexej; Levitt, Malcolm H.
Abstract : A variety of pulse sequences have been described for converting nuclear spin magnetisation into long-lived singlet order for nuclear spin-1/2 pairs. Abstract : A variety of pulse sequences have been described for converting nuclear spin magnetisation into long-lived singlet order for nuclear spin-1/2 pairs. Existing sequences operate well in two extreme parameter regimes. The magnetisation-to-singlet (M2S) pulse sequence performs a robust conversion of nuclear spin magnetisation into singlet order in the near-equivalent limit, meaning that the difference in chemical shift frequencies of the two spins is much smaller than the spin–spin coupling. Other pulse sequences operate in the strong-inequivalence regime, where the shift difference is much larger than the spin–spin coupling. However both sets of pulse sequences fail in the intermediate regime, where the chemical shift difference and the spin–spin coupling are roughly equal in magnitude. We describe a generalised version of M2S, called gM2S, which achieves robust singlet order excitation for spin systems ranging from the near-equivalence limit well into the intermediate regime. This closes an important gap left by existing pulse sequences. The efficiency of the gM2S sequence is demonstrated numerically and experimentally for near-equivalent and intermediate-regime cases.